STUDY OF THE REACTION CROSS SECTION OF 14.0 MeV/u 238U IONS INCIDENT ON 51V TARGET - Sher, G.; Shahzad, M. I.; Ullah, Mati (The Nucleus, 2020)
The reaction cross section of 238U-ions with energy 14.0 MeV /u and incident on a Vanadium target has been investigated using mica track detectors. In this regard, a thin layer (0.56 mg/cm2 ) of V was deposited on a clean and smooth sheet of mica in vacuum. This assembly was then irradiated with a fluence of 0.9Ã—105 ions/cm2 normally incident 238U ions at UNILAC accelerator of G.S.I. Darmstadt, Germany. After irradiation, the target layer was removed from the mica detectors which was then etched in HF acid at room temperature for 20 minutes. After counting the tracks under an optical microscope, the elastic track events were separated from two-prong track events using the angular correlation criterion. Using the number of two-prong inelastic and higher multiplicity track events, the total and partial reaction crosssections were calculated. The experimentally measured total cross section was compared with the cross section calculated using the sharp cut-off model as well as that determined with the quarter-point angle.